(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3KZQ Mhi s)
(3ChdgG (B:s
(3HGH GdMeGSI bGd QLd ef HdYfHQ ef Hfj Jeje jbGd dg bQjW Hf Cfja ESdGej dh cfJ ef eGRf de JSJHM EHdj Hfh GddbjWI ef Pgd Hf TjHGfG s
(3BNQgG (B:s
(3Ydi fZGfZ SGdJ aj jdGYegG cKjQI GdhTi aj djf hJQajb cCfeG djSJ Ch CdHSJ afcG abdUJ MhGTjg Yf GdShb s
(3GdfSNI QhGjI CHj QjGT CMeO Hf CHj gGTes
(3bQFJ GdfSNI Ydi GdTQja CHj JeGe eMeO Hf YHOGdYRjR GdHUQjs
(3fSNI KGfjIs
(3HgG bQGAGJ hebGHdI s
(3hbGHd HgPg GdfSNI CjVkG GdbGVj GdaGVds
(3bQf GdfSN (B:s
Keywords: (3GdCOHs